2008
DOI: 10.1021/jm701195j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cellular Apoptosis with Apoptotic Protease-Activating Factor 1 (Apaf-1) Inhibitors

Abstract: The programmed cell death or apoptosis plays both physiological and pathological roles in biology. Anomalous activation of apoptosis has been associated with malignancies. The intrinsic mitochondrial pathway of apoptosis activation occurs through a multiprotein complex named the apoptosome. We have discovered molecules that bind to a central protein component of the apoptosome, Apaf-1, and inhibits its activity. These new first-in-class apoptosome inhibitors have been further improved by modifications directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Peptoid 1 contains two dichlorophenylethylamino moieties that were found to be important for activity. 128,161 Noticeably, the activators of the Apaf-1 mediated apoptosome assembly, discussed above, reported by Nguyen and Wells 118 also contain a dichlorobenzylamino moiety. Likewise, a halophenyl moiety, in this case bearing a trifluoromethyl group, is also present in the diarylurea derivatives, identified by Lademann et al 158 as inhibitors of the formation of the apoptosome complex.…”
Section: Synthetic Inhibitors Of the Apaf-1-mediated Apoptosome Assemmentioning
confidence: 90%
See 1 more Smart Citation
“…Peptoid 1 contains two dichlorophenylethylamino moieties that were found to be important for activity. 128,161 Noticeably, the activators of the Apaf-1 mediated apoptosome assembly, discussed above, reported by Nguyen and Wells 118 also contain a dichlorobenzylamino moiety. Likewise, a halophenyl moiety, in this case bearing a trifluoromethyl group, is also present in the diarylurea derivatives, identified by Lademann et al 158 as inhibitors of the formation of the apoptosome complex.…”
Section: Synthetic Inhibitors Of the Apaf-1-mediated Apoptosome Assemmentioning
confidence: 90%
“…Confirming this hypothesis, the conformationally restrained mimetic (2 in, 161 QM31 in, 75 now SVT016426; Table I) elicited improved anti-apoptotic activity in an other studied cellular models. 161 Furthermore, SVT016426 was shown to inhibit the release of cytochrome c from mitochondria and suppressed the Apaf-1-dependent intra-S-phase DNA damage checkpoint. 75 The molecular mechanism involved in the anti-apoptotic activity of SVT016326 is currently under study.…”
Section: Synthetic Inhibitors Of the Apaf-1-mediated Apoptosome Assemmentioning
confidence: 99%
“…Other applications of polymer-drug nanoconjugates include rheumatoid arthritis (122), inflammation (123),regenerative medicine e.g. for wound healing (124), ischemia (125) and osteoporosis (126) etc.…”
Section: Polymer-drug Nanoconjugates Targeting Other Diseasesmentioning
confidence: 99%
“…In a process dependent on the hydrolysis of ATP or dATP to ADP or dADP respectively, the Apaf-1-cytochrome c heterodimers assemble into the apoptosome, which provides a platform for the activation of the initiator procaspase-9. Then, the activated caspase-9 cleaves and activates executioner caspases such as caspase-3 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Within this project, we identified some active compounds after screening of a diversity-oriented chemical library of N-alkylglycine oligomers [4]. Then, geometrical restrictions were devised to increase the selectivity [2] by reducing the conformational freedom. A hit compound (1) was obtained [6], and structural studies of 1 showed the presence of cis/trans isomers of the tertiary amide bond exchanging at low rates ( Fig.…”
Section: Introductionmentioning
confidence: 99%